Efficacy and possible mechanisms of topical tranexamic acid in melasma. (1st July 2016) - Kim, S. J.; Park, J.‐Y.; Shibata, T.; Fujiwara, R.; Kang, H. Y.
Summary: Background: Tranexamic acid (TA) has been suggested as an effective treatment for melasma. Aim: To investigate the effects and mechanism of action of topical TA in the treatment of melasma. Methods: In this study, 23 participants with melasma applied a 2% TA formulation to the whole face for 12 weeks. Clinical effects were evaluated using the modified Melasma Area and Severity Index (mMASI) and a chromameter. Skin biopsies were obtained from 10 participants to evaluate pigmentation, vascularity and the expression levels of possible paracrine factors contributing to the effect of TA. Results: Most of the participants had mild melasma, with mMASI of < 5. The mMASI scores significantly improved in 22 of 23 participants after application. The L* values were increased and the a* values were decreased in both lesional and perilesional normal skin. Fontana–Masson staining showed a significant decrease in melanin content in the epidermis. The number of CD31‐positive vessels and the expression of the vascular endothelial growth factor both tended to decrease. Endothelin (ET)‐1 was found to be downregulated with TA. Conclusions: Topical TA is effective for melasma. This immunohistochemical study found that suppression of ET‐1 could be one of the mechanisms of action of TA on melasma.